Market Exploration of MOOC Provider Companies in Indonesia Using Machine Learning - Alwi, Ahmad Chafid; Dwiningrum, Siti Irene Astuti; Priyanto, Priyanto; Nurlayli, Aksin (JURNAL ILMU MANAJEMEN, 2025)
This research aims to explore the market of MOOC (Massive Open Online Course) platform providers in Indonesia using machine learning methods to analyse trends and user behaviour. MOOCs provide broad access to education, especially during the pandemic, where the need for learning flexibility increases. Although machine learning applications have been widely applied in the financial sector, their application in the exploration of the education market, particularly MOOCs, is still minimal. This research aims to address this gap by applying machine learning algorithms, such as clustering and decision trees, to understand user preferences and predict future needs. The study found that Duolingo leads the MOOC market in Indonesia with a 79.76% share. Although the market is dominated by a few big players, there are growth opportunities for new platforms through innovation and proper segmentation. This research also shows the importance of applying AI technology in processing big data to understand market dynamics more comprehensively.